Reproduction performance of sows inseminated with stress gene-free semen given probiotic- supplemented feed - Abela, Julius V. (Annals of Tropical Research, 2020)
This study generally aimed to assess the effect of supplementation with various levels of a novel product containing probiotic and yeast cells, a feed enzyme, short-chain oligosaccharides, and herbal extracts (Farmer Peck’s Performance Booster®) and the use of halothane free gene semen on two successive parities in sows in selected farms in Leyte. Randomized complete block design (RCBD) with treatment used in T0 – (in-feed antibiotics, Og probiotic/kilogram feed and Al using semen from farm’s boar); T1 – (0 antibiotics, 2g probiotic/kilogram feed and Al with halothane free gene semen) and T2 – (0 antibiotics, 3g probiotic/kilogram feed and Al with halothane free gene semen). The study results showed that sow-litter performance of artificially inseminated sows using halothane free gene semen in two farrowing seasons was significantly higher in T1 and T2 groups than that of To group as affected by probiotic supplementation. Probiotic supplementation, both at 2g kg-1 (T1) and 3g kg-1 (T2) of feed is effective in improving both litter and sow performance. The cost of using halothane free gene semen for Al is less as compared to using semen from the farm’s boar, and the cost of using probiotic at two levels as feed additive is relatively lower than using antibiotics based on the pre-weaning mortality, litter size, and litter weight at weaning. The use of halothane free gene semen can now be widely used in the different piggery farms. Including the use of probiotic supplement for both the sows and piglets.